2011
DOI: 10.4306/pi.2011.8.4.372
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic Abnormalities in Clozapine-Treated Patients: A Cross-Sectional Study

Abstract: The objective of our study was to examine the electroencephalogram (EEG) abnormalities associated with clozapine treatment. It was a cross-sectional study on 87 psychiatric patients on clozapine treatment. 32 channel digital EEG was recorded and analysed visually for abnormalities. EEG abnormalities were observed in 63.2% of patients. Both slowing and epileptiform activities were noted in 41.4% of patients. The EEG abnormalities were not associated with dose or duration of clozapine exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…EEG abnormalities such as spikes and sharp waves indicate a increased risk of convulsions. Other studies show that EEG abnormalities may be present without any association with clinical seizures 2527). In this case, while EEG pathology was not detected before starting clozapine, no EEG monitoring was performed while using the drug.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…EEG abnormalities such as spikes and sharp waves indicate a increased risk of convulsions. Other studies show that EEG abnormalities may be present without any association with clinical seizures 2527). In this case, while EEG pathology was not detected before starting clozapine, no EEG monitoring was performed while using the drug.…”
Section: Discussionmentioning
confidence: 69%
“…Also, drugs interfering with cytochrome P450 1A2 may increase or decrease the plasma levels of clozapine. Thus, therapeutic drug monitoring of clozapine has been suggested to predict the onset of seizures 27,29). In case of developing epileptic seizures during clozapine treatment, clozapine dose reduction, changing clozapine with another antipsychotic drug or adding antiepileptics to the treatment are recommended 30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 , 22 24 However, Centorrino et al 21 did not find a relationship between dose and EEG abnormalities. Goyal et al 25 reported EEG abnormalities in 61.9% of patients receiving clozapine at a dose of 100 mg or less. In this study, the mean dose of clozapine at the occurrence of EEG abnormalities varied from 125–600 mg (mean 305 mg/day) and was lower than that in the normal EEG group (mean 378.1 mg/day), albeit not significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Although independently all EEG parameters show worsening, none of these have been found to be significant in predicting response to clozapine on clinical parameters. Although many studies have shown a positive association in this regard[ 26 27 28 ], others have observed negative results. Another study from a cohort of 15 patients reported that EEG abnormalities occurred more frequently (64%) in schizophrenic patients who receive clozapine, yet the EEG changes do not necessarily predict the occurrence of convulsions.…”
Section: Discussionmentioning
confidence: 99%